Uncovering Economic Growth Dynamics: The Role of Idiosyncratic Risk - Asri, Marselinus (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: This study provides a new perspective on the dynamics between foreign direct investment (FDI), idiosyncratic risk, and economic growth in ASEAN countries using structural equation modeling (SEM). It contributes to the literature by highlighting the nuanced role of idiosyncratic risk in shaping regional economic outcomes.Research Objectives: The study aims to examine the direct and indirect impacts of FDI inflows, idiosyncratic risk, and sectoral variables (manufacturing, agriculture, and services) on economic growth in ASEAN from 2013 to 2023.Research Methods: The study uses data from the ASEAN Statistical Database and applies SEM to estimate the relationships between these variables.Empirical Result: The main findings indicate that FDI inflows have minimal impact on idiosyncratic risk, as evidenced by regression coefficients below 0.001 for inward and intra-ASEAN FDI. In contrast, idiosyncratic risk significantly impacts economic growth. The results also reveal that sectoral variables such as manufacturing, agriculture, and services exhibit weaker associations with economic growth.Implications: This information suggests that policymakers should focus on exploiting idiosyncratic risk to improve economic development, while acknowledging the limited direct impact of FDI on risk management, thereby debating more appropriate strategies to promote sustainable economic growthJEL Classification: A11, E60, H11